SOSIALISASI WAJIB SERTIFIKASI HALAL BAGI PELAKU USAHA DI DESA WISATA SURABAYA KEC. SAKRA TIMUR KAB. LOMBOK TIMUR - Rahman, Rahayu Safitri; Malita, Soufa; Warsani, Ziana; Gaffar, Affan; Amrullah, Lalu (Insanta : Jurnal Pengabdian Kepada Masyarakat, 2024)
Indonesia is a country with a Muslim population of 229.62 million people or around 87.2% of the total population. Consuming and using halal products is an obligation that must be carried out by Muslims so that it has become a lifestyle or halal lifestyle. The Indonesian government has issued a law regarding the obligation of halal certification to guarantee the halalness of a product. Socialization to business actors is an activity that must be carried out to provide information and understanding regarding the obligations of halal certification and providing a halal label on every product circulating in Indonesia. The benefits of halal certification and labeling products are that it can increase consumer confidence because it is guaranteed to be halal, has a USP (Unique Selling Point), is able to penetrate the global halal market, increases product marketability in the market, is a cheap investment compared to the revenue growth that can be achieved . Apart from that, registration to apply for halal certification is also relatively easy and fast via the SIHALAL website.